Adsorption of methylene blue and tetracycline onto biomass-based material prepared by sulfuric acid reflux. Issue 57 (19th September 2018) - Islam, Md. Tariqul; Saenz-Arana, Ricardo; Hernandez, Cesar; Guinto, Thomas; Ahsan, Md Ariful; Kim, Hoejin; Lin, Yirong; Alvarado-Tenorio, Bonifacio; Noveron, Juan C.
Abstract : Facile conversion of pine cones into a high-capacity adsorbent for the removal of methylene blue and tetracycline from water. Abstract : The adsorptive removal of environmental pollutants is an effective method for the treatment of contaminated water. Thus, the preparation of adsorbents from low-cost, readily available, and renewable resources has garnered immense attention in recent years. In this study, a facile one-step method for the preparation of a high-capacity adsorbent is demonstrated by refluxing pine cones in concentrated sulfuric acid. With sulfuric acid reflux, the pine cones undergone carbonization as well as functionalization with sulfonic acid groups. The adsorbent demonstrated high adsorption capacity for two emerging organic pollutants, methylene blue (MB) and tetracycline (TC). Different variables such as pH, temperature, contact time, and initial concentration of the pollutants were analyzed and showed that the adsorption capacity for MB increased in a basic pH and vice versa for TC. Also, the elevated temperature favored the adsorption for both MB and TC. The maximum adsorption capacity was found to be 1666.66, and 357.14 mg g −1 for MB and TC, respectively. In comparison to the pristine pine cone, the sulfuric acid treated pine cone demonstrated an extraordinary improvement in the adsorption capacity. The adsorption of MB and TC was performed from the tap water matrix and similar adsorption capacities were found. A packed glass column was also prepared to demonstrate the adsorption of MB from tap water under flow conditions.